A likelihood‐based approach to assessing frequency of pathogenicity among variants of unknown significance in susceptibility genes. (29th October 2020) - Yang, Yunqi; Hong, Christine; Liang, Jane W.; Gruber, Stephen; Parmigiani, Giovanni; Idos, Gregory; Braun, Danielle
Abstract : Commercialized multigene panel testing brings unprecedented opportunities to understand germline genetic contributions to hereditary cancers. Most genetic testing companies classify the pathogenicity of variants as pathogenic, benign, or variants of unknown significance (VUSs). The unknown pathogenicity of VUSs poses serious challenges to clinical decision‐making. This study aims to assess the frequency of VUSs that are likely pathogenic in disease‐susceptibility genes. Using estimates of probands' probability of having a pathogenic mutation (ie, the carrier score) based on a family history probabilistic risk prediction model, we assume the carrier score distribution for probands with VUSs is a mixture of the carrier score distribution for probands with positive results and the carrier score distribution for probands with negative results. Under this mixture model, we propose a likelihood‐based approach to assess the frequency of pathogenicity among probands with VUSs, while accounting for the existence of possible pathogenic mutations on genes not tested. We conducted simulations to assess the performance of the approach and show that under various settings, the approach performs well with very little bias in the estimated proportion of VUSs that are likely pathogenic. We also estimate the positive predictive value across the entire range of carrier scores. We apply our approach to the USC‐Stanford Hereditary Cancer Panel Testing cohort, and estimate the proportion of probands that have VUSs in BRCA1/2 that are likely pathogenic to be 10.12% [95%CI: 0%, 43.04%]. This approach will enable clinicians to target high‐risk patients who have VUSs, allowing for early prevention interventions.